1984
DOI: 10.1007/bf02081863
|View full text |Cite
|
Sign up to set email alerts
|

Urolithiasis in an African population

Abstract: Eighty-one cases of urinary tract calculi in Nigerians seen at the University of Nigeria Teaching Hospital, Enugu, Nigeria, over a period of five years are reviewed. A relative incidence of 13 per 100,000 was established. At the time of presentation, 36 stones were found in the bladder, 21 in the kidneys, 20 in the ureters, one in the prostate and 3 in the urethra. Five patients had calculi at multiple sites. There was a male to female ratio of 5 : 1. Forty-one per cent of the calculi occurred in the 31-40 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
12
1

Year Published

1990
1990
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 10 publications
7
12
1
Order By: Relevance
“…Globally, upper urinary tract stones are more common in contrast to the picture in developing countries where preponderance of lower tract calculi is documented [5,22]. We found the urinary bladder as the commonest site of urinary calculi in our patients.…”
Section: Discussionsupporting
confidence: 39%
See 1 more Smart Citation
“…Globally, upper urinary tract stones are more common in contrast to the picture in developing countries where preponderance of lower tract calculi is documented [5,22]. We found the urinary bladder as the commonest site of urinary calculi in our patients.…”
Section: Discussionsupporting
confidence: 39%
“…Contrary to earlier studies that depicted urinary stone disease as being rare in Nigeria [4][5][6], a number of recent reports have shown an increasing incidence [7][8][9][10][11][12]. Although the reasons for this change in incidence rates remain speculative, rising socioeconomic development and climatic change in the Sub-Saharan nations have been advanced as possible causes [13].…”
Section: Introductionmentioning
confidence: 92%
“…Urolithiasis is said to be rare in Africans [14, 15]. This has been challenged by Mkony et al [16]who reported on stones in 44 adults from Dar es Salaam.…”
Section: Discussionmentioning
confidence: 85%
“…This has been challenged by Mkony et al [16]who reported on stones in 44 adults from Dar es Salaam. In a report from Enugu, Nigeria [14], 14.8% of the urolithiasis patients were children, and the majority of stones were from the bladder. Enugu and Yaoundé are both in the equatorial region; diet, life–styles and socioeconomic development are similar.…”
Section: Discussionmentioning
confidence: 99%
“…This is observed to be higher than the past findings by other researchers[13] in the Southern parts of the country but lower than core Northern Parts of Nigeria. [1112] This may be due to variation of risk factors responsible for urolithiasis formation, especially changing climatic conditions, diet, and drinking habits.…”
Section: Discussionmentioning
confidence: 99%